A new species of Trachytherus (Notoungulata: Mesotheriidae) from the late Oligocene (Deseadan) of Southern Peru and the middle latitude diversification of early diverging mesotheriids - Shockey, Bruce J.; Billet, Guillaume; Salas-Gismondi, Rodolfo (Zootaxa, 2016)
Herein we describe a new species of early diverging mesotheriid notoungulate from the late Oligocene of Moquegua, Peru. This taxon, Trachytherus ramirezi sp. nov., is distinctive in terms of a few characteristics that appear plesiomorphic as compared to those of other described mesotheriids, even other species referred to Trachytherus. Such plesiomorphic traits include the absence of an upper diastema and a lack of heart-shaped incisive foramina, traits that are generally present in other mesotheriids. Our phylogenetic analysis of described early divergent mesotheriids indicates that T. ramirezi was the earliest to diverge. This analysis also confirms the paraphyletic nature of the “genus” Trachytherus. Geographically, T. ramirezi clusters among T. alloxus, T. subandinus, and T. spegazzinianus, all of which are known from a discrete region in the middle latitudes of western South America that we refer to as the Bolivian Orocline Region (BOR). Our palaeobiogeographic reconstruction using maximum parsimony identifies the BOR as a possible ancestral area for the Mesotheriidae and as an important region for their diversification. For the more exclusive Mesotheriinae, the BOR was reconstructed as the ancestral area, an area from which some mesotheriines would have later dispersed to southern South America. Uncertainty concerning the ancestral area, for the Mesotheriidae—which could be BOR or southern South America area (or both)—is possibly due to the ignorance of the phylogenetic affinities for the undescribed mesotheriid remains reported from Tinguirirican localities. The present description of T. ramirezi therefore adds to the high taxonomic diversity of early mesotheriid species in the relatively small area of the BOR and emphasizes the likely role played by this topographically dynamic area on mesotheriid evolution during a significant time in the history of the clade.